A remarkable clinical response in advanced gastric cancer treated with trastuzumab plus capecitabine combination chemotherapy: A report of two cases. Issue 4 (26th February 2019) - Nakamura, Naohiko; Kinami, Shinichi; Fujii, Yoritaka; Miura, Seiko; Fujita, Jun; Kaida, Daisuke; Tomita, Yasuto; Miyata, Takashi; Fujita, Hideto; Ueda, Nobuhiko; Kosaka, Takeo
Key Clinical Message: When trastuzumab + capecitabine and cisplatin chemotherapy could not be conducted continuously because of severe adverse reactions to cisplatin, trastuzumab + capecitabine could be an alternative systemic chemotherapy options for metastatic or recurrent gastric cancer patients. Abstract : When trastuzumab + capecitabine and cisplatin chemotherapy could not be conducted continuously because of severe adverse reactions to cisplatin, trastuzumab + capecitabine could be an alternative systemic chemotherapy options for metastatic or recurrent gastric cancer patients.